Communicative silences in political communication - Mateus, Samuel (2020)
Traditionally, silence has been related to citizen disengagement and disempowerment. Indeed, at first light, the growth of silence is linked to deficits in democracy since silence is understood as passivity while action and speech are the dominant, and sometimes exclusive, modes of political praxis. But silence can mean different things to politics. It can assume a coercive dimension when it is imposed over marginalized groups (the powerless); nevertheless, it can also assume a form of resistance and empowerment when it condenses self-assertion and becomes a form to navigate relations of power. In this paper, we contribute to a politics of silence by examining how silence can be a factor of empowerment and liberty. Focusing on the notion of “communicative silences”, we posit that silence is not a dysfunction of political communication but a significant element of democracy. Far from being a pathology, silence can also be another mode of communication, one that it is separate from speech.